2015
DOI: 10.1016/j.ijpam.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Improving Medication Reconciliation compliance at admission

Abstract: Background and objectivesThe objective of this research is to improve compliance of the medication reconciliation process at the time of patient admission in the Department of Pediatrics at King Faisal Specialist Hospital and Research Centre, Riyadh, Kingdom of Saudi Arabia using an innovative evidence-based approach.Materials and methodsMost of the recent efforts at our institution to revamp the medication reconciliation process have failed. Thus, we implemented an innovative evidence-based approach to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Although educational interventions have been of limited effectiveness, 6 certain individual centres have had success in reducing medication discrepancies by increasing the education of medical residents. 7,8,18 At our institution, increasing resident education to include the full and ongoing process of medication reconciliation, rather than just the technical aspects of completing a BPMH on a preprinted order form, may be of benefit. Mandating access to provincial electronic drug information systems for prescribers, as well as partnering with clinical pharmacists and pharmacy technicians at the time of admission, to facilitate communication with patients' community pharmacies, would result in more complete medication histories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although educational interventions have been of limited effectiveness, 6 certain individual centres have had success in reducing medication discrepancies by increasing the education of medical residents. 7,8,18 At our institution, increasing resident education to include the full and ongoing process of medication reconciliation, rather than just the technical aspects of completing a BPMH on a preprinted order form, may be of benefit. Mandating access to provincial electronic drug information systems for prescribers, as well as partnering with clinical pharmacists and pharmacy technicians at the time of admission, to facilitate communication with patients' community pharmacies, would result in more complete medication histories.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review of medication reconciliation education initiatives targeted toward resident physicians found limited published data on the best way to approach this training. [6][7][8][9][10] Medication reconciliation data for pediatric asthma are limited, as are data assessing the accuracy of medication reconciliation performed by medical residents, given that most studies to date have evaluated pharmacy-led initiatives. 11 Therefore, this study aimed to assess the completeness of medication reconciliation forms prepared by resident physicians for pediatric inpatients with asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Antiepileptic treatment should also be considered for patients with other medical conditions or active epilepsy who do not meet the inclusion criteria. [ 21 ] When necessary, local neurologist experts can be consulted to determine the treatment plan. The treatment and management of such patients can be developed in various localities according to the actual situation.…”
Section: Methodsmentioning
confidence: 99%
“…Patients who meet the inclusion criteria (and are not excluded from the exclusion criteria) and wish to participate may be enrolled for treatment. Antiepileptic treatment should also be considered for patients with other medical conditions or active epilepsy who do not meet the inclusion criteria [21] . When necessary, local neurologist experts can be consulted to determine the treatment plan.…”
Section: Methodsmentioning
confidence: 99%
“…7 Another study showed that hands-on interactive training sessions, close monitoring, reinforcement by assigned physicians and audit reports in a hospital in Saudi Arabia improved admission medication reconciliation remarkably in 2015. 4 A hospital in Abu Dhabi improved its medication reconciliation compliance from 40% to 85% in 2014-2015 over 15 months by sharing daily audit reports of admission medication reconciliation, awareness and education regarding filling of online reconciliation forms, mandatory electronic hands-on training for the newly hired physicians for filling the forms and screening of all admissions for medication reconciliation the following morning. 8 Studies indicate that medication reconciliation performed by a clinical pharmacist can significantly reduce medication discrepancies.…”
Section: Open Accessmentioning
confidence: 99%